2022
DOI: 10.1002/acr2.11413
|View full text |Cite
|
Sign up to set email alerts
|

47XXY and 47XXX in Scleroderma and Myositis

Abstract: Objective We undertook this study to examine the X chromosome complement in participants with systemic sclerosis (SSc) as well as idiopathic inflammatory myopathies. Methods The participants met classification criteria for the diseases. All participants underwent single‐nucleotide polymorphism typing. We examined X and Y single‐nucleotide polymorphism heterogeneity to determine the number of X chromosomes. For statistical comparisons, we used χ2 analyses with calculation of 95% confidence intervals. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Exceptions are autoimmune diseases like ankylosing spondylitis and Goodpasture's disease, which are not seen more frequently among KS males (7). A likely explanation KS males are known to have impaired bone metabolism, reduced bone mass density (BMD) (11), and a prevalence of osteoporosis of 5-10% and approximately 40% for osteopenia (12). Relative or manifest hypogonadism and a higher prevalence of metabolic syndrome are some factors that potentially decrease BMD.…”
Section: Morbidity and Mortality In Klinefelter Syndromementioning
confidence: 99%
“…Exceptions are autoimmune diseases like ankylosing spondylitis and Goodpasture's disease, which are not seen more frequently among KS males (7). A likely explanation KS males are known to have impaired bone metabolism, reduced bone mass density (BMD) (11), and a prevalence of osteoporosis of 5-10% and approximately 40% for osteopenia (12). Relative or manifest hypogonadism and a higher prevalence of metabolic syndrome are some factors that potentially decrease BMD.…”
Section: Morbidity and Mortality In Klinefelter Syndromementioning
confidence: 99%
“…While these differences are partly attributable to sex hormones, X-linked factors represent other likely contributors (1)(2)(3)(4)(5)(6). Men with Klinefelter's syndrome, who bear an extra X chromosome (47,XXY) in a male hormonal context, have a risk equivalent to women to develop relatively rare immune disorders such as systemic lupus erythematosus (SLE) (7), Sjogren's syndrome (8), or Systemic Sclerosis (9). Moreover, the female bias in autoimmune diseases such as SLE is observed before puberty (10).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting finding was also found through the characterization of patients with both IMDs and sex-chromosome trisomies. A study by Scofield et al [53] revealed an association of the Klinefelter syndrome (47, XXY) with SSc and idiopathic inflammatory myopathies.…”
Section: Studying Patients With Disease Complications and Non-europea...mentioning
confidence: 99%